From studies on the thrust in swimming - Lutomski, P.; Stankowski, T.; Jan, K.; Pietrusik, K.; Ciereszko, A.; Strzelczyk, R. (Journal of Human Sport & Exercise, 2008)
Swimming speed is determined by many factors, including weight preparation of the swimmer which is one of the most important ones. This power is directly related to the speed a swimmer can reach in water, that is the value of thrust. The aim of the study was to establish the level of thrust and swimming speed of the 2nd year students (n=20) of the University School of Physical Education (USPE) in Poznan and to compare them with the results of study from 1983 in which the 4th year students (n=20) of the USPE in Poznan were studied. The current study was carried out in the context of the long-term changes in swimming technique. Research methods: measurement of thrust in real conditions was performed using a prototype device for the measurement of thrust of a swimmer which makes it possible to register the force in the water environment; swimming speed was established on the basis of the time needed to cover the distance of 25 metres, according to the regulations of the Polish Swimming Association. Conclusions: the students taking part in the 1983 study had higher values of thrust, but a lower speed than the students taking part in the 2006 study, which suggests that apart from the thrust the technique of swimming has a important influence of the swimming speed.